Environmental monitoring with the help of Internet of Things (loT) and machine learning - Alam, Md. Sakirul; Ahsan, Farshid; Sarker, Anik (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.